Structure of the formation of a classification description of forest rakes - Platonov Alexey (BIO Web of Conferences)
When performing work related to the proper maintenance of a number of infrastructure facilities, the structure of technological processes often provides for the technological operation of collecting and raking logging residues, carried out by mechanization. The article discusses the issues of classification of technical means of mechanization of performing these works, provides a formula for creating a description of technical means of mechanical removal of logging residues, considers the sequence of formation of a classification description of specific models of forest rakes, provides examples of their classification, and formulates a conclusion about the creation of a unified approach to systematization of produced forest rakes.